Prevention of religious extremism among young people (Journal of actual problems of jurisprudence, 2019)
The purpose of this article indicate the necessity of further improvement of a state policy in the field ofreligion at observance of the principles of secular character of the state, fundamental human rights andpositive change of a religious situation in the country, preventions and prevention of manifestation ofreligious extremism among the youth generation.Keywords: extremism, terrorism, youth, prevention.